2018
DOI: 10.1007/s00338-018-1714-x
|View full text |Cite
|
Sign up to set email alerts
|

Meiofauna associated with vermetid reefs: the role of macroalgae in increasing habitat size and complexity

Abstract: We present the first dataset of meiofauna associated with vermetid reefs (biogenic constructions of Mediterranean intertidal habitat) in two areas along the northern coast of Sicily, Italy. The vermetid reefs are characterized by a horizontal extension from the shore towards the open sea and can be divided into three zones (the inner margin, the cuvette zone and the outer margin) which differ in hydrodynamic features. We studied the spatial distribution of meiofauna along the horizontal axis of the vermetid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 59 publications
(116 reference statements)
4
11
0
Order By: Relevance
“…Our findings also demonstrate that the distance between the vermetid bioconstructions plays a major role in forming different assemblages from site to site, confirming the existence of a geographical variability of benthic fauna at medium spatial scale, possibly due to biogeographic factors associated with the local variation of the environmental parameters [40,51]. Moreover, macroalgae provide additional substrate for grazer gastropods, in agreement with Ape et al [52] who found a significant relation between meiofauna and algal community associated with vermetid bioconstructions.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings also demonstrate that the distance between the vermetid bioconstructions plays a major role in forming different assemblages from site to site, confirming the existence of a geographical variability of benthic fauna at medium spatial scale, possibly due to biogeographic factors associated with the local variation of the environmental parameters [40,51]. Moreover, macroalgae provide additional substrate for grazer gastropods, in agreement with Ape et al [52] who found a significant relation between meiofauna and algal community associated with vermetid bioconstructions.…”
Section: Discussionsupporting
confidence: 91%
“…This general pattern is also consistent and has already been registered separately for each of the main associated groups: for mollusks, a higher abundance, species diversity, and functional diversity were observed for assemblages associated with morphologically more complex macroalgae (Chemello & Milazzo, 2002;Veiga et al, 2018;Barbosa et al, 2019 andDuarte et al, 2020); for crustaceans, similar results were found for amphipods in Sargassum beds, presenting higher abundance and diversity in association with higher biomass and/or more complex fronds (Carvalho et al, 2018;Kodama et al, 2020); and for polychaetes, a higher abundance and diversity was observed when in association with increased biomass of an invasive macroalgae (Box et al, 2010). These positive effects are also observed in smaller organisms, such as meiofaunal assemblages, which are influenced by the macroalgal cover (Ape et al, 2018;Hicks, 1980;Losi et al, 2018). Ape et al (2018) observed positive correlation between meiofaunal total abundance and habitat size, but its effect was dependent on macroalgal identity, with higher total abundance of meiofauna on alga that presented more complex architecture, in terms of both biomass and their fractal dimensions.…”
supporting
confidence: 65%
“…These positive effects are also observed in smaller organisms, such as meiofaunal assemblages, which are influenced by the macroalgal cover (Ape et al, 2018;Hicks, 1980;Losi et al, 2018). Ape et al (2018) observed positive correlation between meiofaunal total abundance and habitat size, but its effect was dependent on macroalgal identity, with higher total abundance of meiofauna on alga that presented more complex architecture, in terms of both biomass and their fractal dimensions. Thus, based on niche theory, which argues that more complex habitats provide more microenvironments or niches (Loke & Todd, 2016), and given the intimate relationship between the associated fauna and the algal substrate (Christie et al, 2009), it would be expected that fluctuations on the algal substrate would be followed by the fauna; however, this is not so obvious.…”
mentioning
confidence: 87%
“…Moreover, differences in macroalgal complexity could explain differences in meiofaunal community (Gibbons, 1988b;Warwick, 1994a, 1994b): more complex macroalgae increase meiofaunal abundance and diversity by offering a large number of habitats where to feed and live, a high variety of food resources, facilitating the amount of trapped sediment and detritus, and providing effective shelter against predation (Whatley and Wall, 1975;Hicks, 1980Hicks, , 1985Hull, 1997;Frame et al, 2007). The macroalgal size is another factor that influences the structure of meiofaunal assemblages (Hicks, 1980;Gunnill, 1982), but its effect seems to be dependent on macroalgal identity; this in turn may be attributable to differences of complexity between macroalgae (Veiga et al, 2016;Ape et al, 2018). The three-dimensionally shaped erect macroalgae belonging to Ochrophyta found in the present study showed a higher complexity compared to that of Rhodophyta, which were composed by a great number of encrusting algae, with a more bidimensional shape.…”
Section: Meiofaunal Patterns and Relation With The Sessile Macrobenthosmentioning
confidence: 99%
“…Most previous studies on hard bottom meiofauna focused on the phytal meiofauna, and especially to the fraction living on macroalgae, while the meiofauna associated with the surfaces beneath the algal canopy or to other sessile organisms has received little attention Griffiths, 1986, 1988;Gibbons, 1988aGibbons, , 1988bArroyo et al, 2004;Fraschetti et al, 2006;Danovaro et al, 2007;Logan et al, 2008;Russo et al, 2015;Ape et al, 2018). Moreover, most studies have been conducted in the intertidal and upper sublittoral zones (e.g.…”
Section: Introductionmentioning
confidence: 99%